REVIEW OF THE EFFECT OF SLUICE BOX SUPPORTING PARAMETERS ON THE RECOVERY RESULTS OF METAL MINERAL PROCESSING - Afroza Pratiwi; Edy Nursanto; Eddy Winarno (Sean Institute, 2023)
This mineral processing aims to remove valuable minerals and impurities using mechanical means by utilizing the physical and chemical properties of minerals. One of them is using gravity’s concentration with a sluice box. This tool requires supporting parameters for optimal recovery including dimensions and material, riffle, slope, air discharge and type of carpet to achieve the desired recovery. The purpose of this paper is to find out whether it is true that some of these supporting parameters affect the metal mineral processing results with the limitation of the problem being the influence of supporting parameters in various previous research results. The results of the review show that the supporting parameters affect the processing results. In addition, the parameters also influence each other. If the results of these parameters are not correct, then the processing results will also not be optimal and material deposition will occur.